Chasing Lincoln's killer - Swanson, James L., 1959- (Scholastic Press, 2009)
Recounts the twelve-day pursuit and capture of John Wilkes Booth, covering the chase through Washington D.C., Maryland, and Virginia, with a discussion of Abraham Lincoln as a father, husband, and friend that examines the impact of his death on those close to him.